A Structured Review of Antithrombotic Therapy in Peripheral Artery Disease With a Focus on Revascularization: A TASC (InterSociety Consensus for the Management of Peripheral Artery Disease) Initiative. Issue 25 (20th June 2017) - Hess, Connie N.; Norgren, Lars; Ansel, Gary M.; Capell, Warren H.; Fletcher, John P.; Fowkes, F. Gerry R.; Gottsäter, Anders; Hitos, Kerry; Jaff, Michael R.; Nordanstig, Joakim; Hiatt, William R.
Abstract : Peripheral artery disease affects >200 million people worldwide and is associated with significant limb and cardiovascular morbidity and mortality. Limb revascularization is recommended to improve function and quality of life for symptomatic patients with peripheral artery disease with intermittent claudication who have not responded to medical treatment. For patients with critical limb ischemia, the goals of revascularization are to relieve pain, help wound healing, and prevent limb loss. The baseline risk of cardiovascular and limb-related events demonstrated among patients with stable peripheral artery disease is elevated after revascularization and related to atherothrombosis and restenosis. Both of these processes involve platelet activation and the coagulation cascade, forming the basis for the use of antiplatelet and anticoagulant therapies to optimize procedural success and reduce postprocedural cardiovascular risk. Unfortunately, few high-quality, randomized data to support use of these therapies after peripheral artery disease revascularization exist, and much of the rationale for the use of antiplatelet agents after endovascular peripheral revascularization is extrapolated from percutaneous coronary intervention literature. Consequently, guideline recommendations for antithrombotic therapy after lower limb revascularization are inconsistent and not always evidence-based. In this context, the purpose of this structured review is to assess the available randomized data for antithrombotic therapy after peripheral arterial revascularization, with a focus on clinical trial design issues that may affect interpretation of study results, and highlight areas that require further investigation. Abstract : Supplemental Digital Content is available in the text.